Unjuk Kerja Performa Turbin Arus Laut Sumbu Vertikal Pada Berbagai Bentuk Sudu Unik - Rizki Mendung Ariefianto; Rini Nur Hasanah; Wijono Wijono (Rekayasa, 2022)
Efficiency and self-starting capability performances are the main problems in vertical axis turbines. By purposing improves its performance, vertical axis turbines have been developed with various models. One of the developments of this model is to design the turbine blades into unique shapes. This research aims to determine the performance of some unique blade vertical axis turbines conditioned on the same parameters, especially if applied in a marine environment. Turbines with helical blade (HB), eggbeater-shaped blade (ESB), diamond-shaped blade (DSB), Y-shaped blade (YSB), and arrow-shaped blade (ASB) were investigated based on efficiency and self-starting capability using QBlade software. Good performance symmetrical foils such as NACA 634021 are also applied to each turbine. The simulation results show that from the aspect of efficiency performance, turbine ASB more than HB more than ESB more than DSB more than YSB. Meanwhile, in the aspect of self-starting capability performance, the sequence is similar to efficiency performance, based on the two approaches applied. The highest efficiency achieved by the ASB turbine is 0.391 at the lowest tip speed ratio of λ = 4. The ASB turbine also achieves the best self-starting performance, which has a minimum static torque coefficient of 0.00155 and can produce the required power at the lowest marine current speed of 0.806 m/s. This performance brings the ASB turbine to produce a rated power of 52.52 kW, or more than twice the power production of the lowest efficiency turbine and has an average power gain of 3.75 kW per 0.2 m/s.